Neuraxial Cytokines in Pain States - Gonçalves dos Santos, Gilson; Delay, Lauriane; Yaksh, Tony L.; Corr, Maripat (Frontiers in Immunology, 2020)
A high intensity potentially tissue injuring stimulus generates a homotopic response to escape the stimulus and is associated with an affective phenotype considered to represent pain. In the face of tissue or nerve injury, the afferent encoding systems display robust changes in the input-output function leading to an ongoing sensation reported as painful and sensitization of the nociceptors such that an enhanced pain state is reported for a given somatic or visceral stimulus. Our understanding of the mechanisms underlying this nonlinear processing of nociceptive stimuli has led to our appreciation of the role played by the functional interactions of neural and immune signaling systems in pain phenotypes. In pathological states, neural systems interact with the immune system through the actions of a variety of soluble mediators, including cytokines. Cytokines are recognized as important mediators of inflammatory and neuropathic pain, supporting system sensitization and the development of a persistent pathologic pain. Cytokines can induce a facilitation of nociceptive processing at all levels of the neuraxis including supraspinal centers where nociceptive input evokes an affective component of the pain state. We review here several key pro-inflammatory and anti-inflammatory cytokines/chemokines and explore their underlying actions at four levels of neuronal organization: 1) peripheral nociceptor termini; 2) dorsal root ganglia; 3) spinal cord and 4) supraspinal areas. Thus, current thinking suggests that cytokines by this action throughout the neuraxis play key roles in the induction of pain, the maintenance of the facilitated states of pain behavior generated by tissue injury/inflammation and nerve injury.